EVALUASI KINERJA SISTEM IRIGASI (Studi Kasus Pada Daerah Irigasi Manganti Kabupaten Ciamis dan Kabupaten Cilacap) - reyhandhita soesantho, audi; defiana, yanti; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2024)
Evaluation of the performance of an irrigation system is needed to determine the value of all supporting components of the irrigation system which then becomes a reference for improvement. The evaluation of irrigation system performance refers to PUPR Minister Regulation No. 12/PRT/M/2015 concerning Operation and Maintenance of Irrigation Network combined with Subak irrigation network system. Manganti Irrigation Area has an area of 26,153.00 Ha. There is a problem of less than optimal performance of the irrigation system of the Manganti Irrigation Area in 2022. This study aims to evaluate the performance of the D.I Manganti irrigation system. In this study, a qualitative descriptive method was used, by collecting primary data using a structured form of maintenance based on evaluating the performance of the irrigation system by means of manual calculations using Microsoft Excel. The results of the analysis of the value of the irrigation system performance index have a value weight of 73.88% according to regulatory standards with a range of values of 70-79 including in the category of good performance, therefore it still needs maintenance, routine maintenance and periodic maintenance to avoid a decrease in the value of the irrigation system performance index, this can affect the condition and function of the D.I Manganti irrigation system.